2016
DOI: 10.1038/srep20534
|View full text |Cite
|
Sign up to set email alerts
|

Detecting O2 binding sites in protein cavities

Abstract: Internal cavities are important elements in protein structure, dynamics, stability and function. Here we use NMR spectroscopy to investigate the binding of molecular oxygen (O2) to cavities in a well-studied model for ligand binding, the L99A mutant of T4 lysozyme. On increasing the O2 concentration to 8.9 mM, changes in 1H, 15N, and 13C chemical shifts and signal broadening were observed specifically for backbone amide and side chain methyl groups located around the two hydrophobic cavities of the protein. O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 63 publications
3
39
1
Order By: Relevance
“…The D/G, D/F/G, and H/J openings (Fig. 5) have also been previously simulated in the egress and ingress of molecular oxygen (31). Although the openings through the D/F/G pocket are larger and able to accommodate benzene, the H/J and D/G pockets form narrower surface openings that cannot, suggesting that different ligands may bind to the buried cavity through different pathways.…”
Section: Dynamic Fluctuation Of the Buried Cavity Of L99amentioning
confidence: 62%
See 1 more Smart Citation
“…The D/G, D/F/G, and H/J openings (Fig. 5) have also been previously simulated in the egress and ingress of molecular oxygen (31). Although the openings through the D/F/G pocket are larger and able to accommodate benzene, the H/J and D/G pockets form narrower surface openings that cannot, suggesting that different ligands may bind to the buried cavity through different pathways.…”
Section: Dynamic Fluctuation Of the Buried Cavity Of L99amentioning
confidence: 62%
“…Initial crystal structures of the L99A mutant indicate that the~40 Å 3 cavity in the C-terminal domain of wild-type protein expands to an~150 Å 3 cavity (26), a volume capable of accommodating substituted benzenes and noble gases (20,24,(27)(28)(29)(30). O 2 is simulated to bind and escape the buried cavity through openings between the D, E, G, H, and J helices (31), whereas binding of substituted benzenes is accompanied by discrete rearrangements in the F and G helices (30). Substantial rearrangements also occur in these helices in an excited state that comprises~3% of the protein ensemble at room temperature (5,25).…”
Section: Introductionmentioning
confidence: 99%
“…At one, cluster A1 on the agonist-free β 2 adrenergic receptor (Table 1), the cholesterol ring system is buried in a cleft in the protein surface (Fig. 1C) gases in small hydrophobic protein cavities [42], the binding of small organic molecules in the hydrophobic cavity of bee odorant binding protein [43] and the binding of general anaesthetics to pentameric ligand-gated ion channels [40], binding in all these cases affecting protein function. The fact that we find differences in the deep cholesterol interactions with the agonist-free and bound forms of both the β 2 adrenergic and the A 2A adenosine receptors (Table 1) suggests that interaction with deep cholesterol molecules could affect receptor function.…”
Section: The Nature Of the Deep Binding Sitesmentioning
confidence: 99%
“…The association of O 2 with WT* was studied by solution NMR spectroscopy at an O 2 concentration range of 0.27–8.9 mM. All measurements were initiated >19 h after changing the gas pressure, because 19 h was required to reach a new gas dissolution equilibrium in the NMR tube when studying the L99A mutant protein in which larger NMR spectrum changes were observed . Figure shows 1 H/ 15 N HSQC and 1 H/ 13 C CT‐HSQC spectra of the protein at different O 2 concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…NMR provides a high‐resolution approach to investigate the structure and dynamics of proteins in solution. Several studies have shown that NMR spectroscopy in combination with dioxygen (O 2 ) gas‐pressure is a powerful tool for investigating the location of internal protein cavities and pockets in solution and their accessibility to ligands, owing to the paramagnetic properties of O 2 . In previous studies, methods to analyze O 2 ‐binding sites in proteins in solution were reported, using the O 2 ‐induced enhancement of backbone amide proton spin‐lattice relaxation .…”
Section: Introductionmentioning
confidence: 99%